Forecasting Training with POM-QM Software for Windows in Solving Dynamic and Fast Problems in the World of Work - Marendra, I Gede; Aryata, I Made; Afghani, Irmawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
A forecasting training program using POM-QM for Windows was conducted to enhance students' skills in forecasting as a strategic approach to tackle challenges in the dynamic workforce. Organized as part of Community Service Activities (PKM) by Pamulang University in collaboration with the University of Serang Raya, the training introduced forecasting concepts, methods like moving averages and exponential smoothing, and their application using POM-QM software. Through lectures, simulations, and case studies, participants gained a deeper understanding of analyzing historical data for decision-making. Evaluation results showed participants could independently use the software for various business scenarios. This training contributed positively to participants' skill development and is anticipated to serve as a sustainable model for enhancing workforce competitiveness in the digital era.